Persecution of the Indonesian Ahmadiyya Congregation through the MUI Fatwa, Tuan Guru, and the Lombok Community - Abdul Gaffar (UIN Sjech M. Djamil Djambek Bukittinggi, 2023)
Ahmadiyya has taken refugee in the Transito Dormitory since the end of 2005 and 2010. They tried to return to their homes in West Lombok but drove out by the community. This article will discuss Ahmadiyya, who experienced persecution in Lombok, and the basis for the MUI to issue deviant fatwas against the Ahmadiyya Congregation in 1980 and 2005. The process of the persecution of the Ahmadiyya in Lombok and the influence of the Majelis Ulama Indonesia and Tuan Guru on society are revealed in this study. The theories of Louis Althusser about state ideological institutions, in this case, the Majelis Ulama Indonesia, and Johan Galtung's theory about direct violence perpetrated by the community and indirect violence through the SKB 3 Menteri (Joint Decree of Three Ministers) being operate in this study. The research uses in-depth interviews with Ahmadiyya members in the Mataram Transito Dormitory. This study finds that the MUI Fatwa serves as legitimacy for society in carrying out violence and persecution of the Lombok Ahmadiyya Congregation and the influence of Tuan Guru through their daily life and lectures at the mosque.